Success Factors of Small and Medium-Sized International Enterprises in the Chinese Market from the Perspective of Polish Direct Investment (Cultural Approach); Czynniki sukcesu małych i sŕednich przedsiebiorstw miedzynarodowych na rynku chinśkim z perspektywy polskich inwestycji bezposŕednich (ujecie kulturowe) - Krystyna Iwinśka-Knop; Jarosław Linka (Comparative Economic Research. Central and Eastern Europe, 2011)
Globalization has resulted in increasing transfer of firms operations, regardless of their size, to other countries. The recent dynamic emergence of China in the global economy, connecting with the vast inflows of foreign direct investment in their territory and common adjustments problems of many Western companies, has resulted in growing interest for best suitable business practices to this culturally and socially different environment. In this article, the key factors critical to the success of international companies in this region are introduced, with particular consideration to indigenous cultural elements and specific operation requirements of small and medium-sized enterprises in Business-to-Business sectors. The presented information are based on the broad literature review, five years of direct observation and thirty eight interviews conducted with Polish managers directly residing in China. In addition, some practical recommendations for managers and further research are given. – – Globalizacja wymusza na firmach, niezalezṅie od ich wielkosći, coraz czestsze przenoszenie operacji do innych krajoẃ. Dynamiczne pojawienie sie Chin w sẃiatowej gospodarce i szeroki napływ zagranicznych inwestycji bezposŕednich na ich teren oraz problemy adaptacyjne wielu zachodnich przedsiebiorstw, spowodowały zainteresowanie najlepszymi praktykami biznesowymi dostosowanymi do tego odmiennego kulturowo i społecznie otocznia. W artykule zaprezentowane zostały najwazṅiejsze czynnik majace wpływ na osiagniecie sukcesu przez firmy miedzynarodowe na tym obszarze, ze szczegoĺnym uwzglednieniem aspektoẃ kulturowych i specyfiki działania małych i sŕednich podmiotoẃ na rynkach B2B. Prezentowane informacje sa oparte na przegladzie literatury, piecioletnich obserwacjach bezposŕednich oraz trzydziestu osḿiu wywiadach przeprowadzonych z menadzėrami polskich przedsiebiorstw odpowiedzialnymi za operacje w Chinach. Dodatkowo wskazano kilka praktycznych rekomendacji menadzėrskich oraz mozl̇iwosći dalszych badan\'.
Keywords: 330